The Evolution of Alexia in Two Cases of Posterior Cortical Atrophy - Eleonora Catricalà; Pasquale A. Della Rosa; Paola Ortelli; Valeria Ginex; Alessandra Marcone; Daniela Perani; Stefano F. Cappa (Behavioural Neurology)
Posterior cortical atrophy (PCA) is an uncommon presentation of Alzheimer's disease (AD), characterised by prevalent anatomo-functional involvement of posterior cortical areas. Accordingly, the main clinical features at onset are disorders of high-order visual processing, such as alexia and impairments of visuo-spatial and visuo-constructional abilities. The clinical features in the early stages of disease are variable, and they have been suggested to stem from prevalent ventral or dorsal brain pathology, and/or asymmetric hemispheric involvement. With disease progression, these differences tend to blur with the increasing severity of neuropsychological dysfunction. We report two PCA patients showing different patterns of reading impairment (respectively, letter-by-letter reading and neglect dyslexia). A follow-up study suggested that the qualitative features of alexia remain distinctive with disease evolution. In addition, single photon emission tomography (SPECT) studies revealed different patterns of hypoperfusion, consistent with the alexia types. A careful reading assessment can provide important insights to the pattern of progression of the disease in patients with PCA up to the late stages of the pathology.